Efeitos da ovariectomia sobre o tecido pulpar de dentes traumatizados e submetidos a movimentação dentária induzida - Lucietto, Gabrielle (2020)
Orthodontically induced tooth movement produces changes in periodontal tissues and in the detinopulpar complex. The structural and functional normality of these tissues seems to be influenced by local and systemic factors, and the clinical detection of changes depends on the type, duration and intensity of the stimulus applied. Studies reveal the occurrence of several biological reactions during induced tooth movement, including increased or reduced blood flow and cellular changes. In addition, the patient's hormonal status has a great impact on the orthodontist's conduct, since it can directly influence the success of the treatment. Estrogen is the main female steroid sex hormone and its reduction is associated with a decrease in alveolar bone mineral density, which can significantly increase the speed of tooth movement and can also influence the occurrence of root resorption. Thus, the aim of this study was to evaluate the effects of ovariectomy associated with dental trauma, and its influences on the histological structure of the pulp dentin complex during induced tooth movement in rats. 48 rats (Wistar) were used, separated into eight experimental groups, with 6 animals in each: Group 1 - control (G1): composed of animals that were not submitted to any experimental procedure; Group 2 (G2): composed of animals submitted to dentoalveolar trauma (DT); Group 3 (G3): composed of animals submitted to ovariectomy (OVX); Group 4 (G4): composed of animals submitted to DT and OVX; Group 5 (G5): composed of animals submitted to induced tooth movement (IDT); Group 6 (G6): composed of animals submitted to IDT and DT; Group 7 (G7): composed of animals submitted to ITM and OVX and Group 8 (G8): composed of animals submitted to ITM, DT and OVX. At the end of the experimental period, the animals were euthanized and the jaws removed, fixed in 10% formaldehyde, decalcified, included in paraplast, cut at 5μm and stained with hematoxylin and eosin. The rate of tooth movement was verified, measuring the distance between the mesial surface of the 1st molar and the distal one of the upper 3rd molar. Histopathological assessments of pulp tissue were performed, through histological analysis of the cellular pattern, dystrophic changes, hemodynamic changes and dentinal changes. The rate of tooth movement was significantly higher in animals in the ITM + DT + OVX group when compared to the other groups (p <0.05). There were no changes in the cellular pattern of pulp tissue in the different experimental groups. In the analysis of dystrophic changes, only the G7 (ITM + OVX) and G8 (ITM + DT + OVX) groups presented some areas of hyalinization. Regarding hemodynamic changes, vascular congestion and thrombosis were similar in all groups, while hemorrhage was not observed in any group. The only change in dentin observed was internal root resorption, present in animals in groups G4 (DT + OVX), G5 (ITM), G7 (ITM + OVX) and G8 (ITM + DT + OVX). The MDI group showed greater resorption areas than the ITM + DT and ITM + TD + OVX groups and the IDM + OVX group showed the highest amounts of root resorption areas when compared with all experimental groups. We conclude that the induced tooth movement associated with dentoalveolar trauma and ovariectomy, induces a higher rate of tooth movement, and greater occurrences of pulp tissue hyalinization, however the largest areas of internal root resorption were found in the ITM + OVX group